Technologies for automation creation of an ontology of urbanonyms in the aspect of historical changes (on the example of Almaty). Issue 1 (January 2021) - Barakhnin, Vladimir; Mansurova, Madina; Dossanov, Bekzhan; Kyrgyzbayeva, Marzhan
Abstract: When creating geoinformation systems of a city scale, relation this or that information from Internet, there comes the task of creation an ontology of urbanonyms taking into account their historical changes. The account of historical changes is necessary, for example, to process messages about urban event from blogs: since more and more representatives of the middle and older generations are becoming active Internet users, the massages often contain the former names of urbanonyms. Let us note that it is the accounting of historical changes that is required to solve this problem that determines the need to create not a thesaurus, which is sufficient, as shown in [1], to take into account geographical names commonly used (at least in natural science articles) in their actual from, but an ontology. Taking into account the specifics of the task of creating an ontology of Almaty, in should be bilingual: in the Kazakh and Russian languages.